Causes of Delay in the Construction Projects of Subway Tunnel - Dingbang Zhang; Hang Zhang; Tao Cheng (Advances in Civil Engineering)
The constructions of urban infrastructure are an important sector that provides remarkable ingredients for the economic development of modern cities. However, a large number of transportation infrastructure construction projects are delayed; therefore, those projects always exceed their original time and cost estimates. So construction delay has been considered as a recurring problem in the construction projects of urban infrastructure, and it adversely affects the time, cost, safety, and quality of construction. This paper is committed to investigating the time performance of subway tunnel constructions in China to identify the causes of delay based on the questionnaire surveys of 87 tunnel consultants and 91 contractors, and a total of 49 delay causes of tunnel construction are identified one by one in this study. It can be concluded from this study that the six most severe delay causes are national policy for subway tunnel construction, complicated geological conditions, payment delays by owners, award projects to the lowest bid price, shortage of advanced large equipment, and low productivity of laborers. There is a relatively reliable agreement between the tunnel consultants and contractors of 76.3% on the ranking of different delay causes.